Assessment of Lead (Pb) Remediation Potential of Senna obtusifolia in Dareta Village, Zamfara, Nigeria - Udiba, Udiba Ugumanim (J Health Pollut, 2020)
BACKGROUND. Environmental contamination by lead (Pb) and other toxic metals is of significant environmental and human health concern. Heavy metals are not readily eliminated by degradation, and thus remediation of contaminated media (soil, sediment and water/sludge) requires the outright removal or cleanup of these metals. Evaluation of the performance and cost efficiency of various remediation methods has led to the development of bioremediation as an inexpensive, innovative and environmentally friendly cleanup strategy. OBJECTIVES. The present study was designed to assess the Pb remediation potential of wild Senna obtusifolia (Sicklepod), in Dareta Village, Zamfara, Nigeria. METHODS. Soil and Senna obtusifolia samples were collected from established plots and Pb content was determined using a Shimadzu atomic absorption spectrophotometer (model AA-6800, Japan) after wet digestion. RESULTS. The mean concentrations of Pb (mg/kg) in soil, roots, stems and leaves, respectively, were 130.68±5.2, 61.33±17.86, 66.64±18.10 and 173.39±13.73 for plot 1, 287.84±6.5, 69.42±11.62, 123.4±3.67 and 294.28±4.38 for plot 2, 315.73±4.13, 68.42±10.22, 86.89±6.08 and 290.61±7.47 for plot 3, 396.86±5.48, 91.64±2.87, 150.58±2.21 and 282.53±5.69 for plot 4 and 264.23±8.02, 72.71±2.18, 124.60±2.27 and 282.40±3.79 for plot 5. Average values for the translocation factor, bioaccumulation factor and bioconcentration factor were 3.65±0.66, 1.01±0.23 and 0.29±0.10, respectively. DISCUSSION. Soil Pb levels in the present study were found to be within the United States Environmental Protection Agency (USEPA) standards and the Dutch Intervention Values for Pb in soil. Lead content of Senna obtusifolia leaves was found to be higher than the Pb content of the stem and root, indicating relatively low restriction and the efficiency of internal transport of the toxic metal from the roots towards the aerial parts. High translocation and bioaccumulation factors indicate that the plant has vital characteristics for phytoextraction of Pb. The mean Pb concentration of Senna obtusifolia leaves was found to be far above Codex general standards and the European Union (EU) maximum levels for Pb in leafy vegetables. CONCLUSIONS. The study concludes that wild Senna obtusifolia has significant characteristics for phytoextraction of Pb and that consumption of Senna obtusifolia leaves from the study area would pose a serious risk of Pb intoxication. COMPETING INTERESTS. The authors declare no competing financial interests.